Strategic Management Approaches and the Realization of Business Identity: Perspective from Italy - Tabucchi, Dante Levi; Manzoni , Calvino M.; Casanova, Fleur G. (Journal of Strategic Management, 2022)
Establishing a strong brand identity allows business to set differentiation, personality, consistency, awareness, and loyalty among customers. An organization’s brand is its identity, and this image will be portrayed to all employees and customers-therefore making it one of the business’ most valuable assets. It is also paramount to note that, business identity is an essential reason why many companies stand out from their competition. A strong business identity helps an organization set itself apart from its competitors and maintain a personality that the public can easily associate the brand. It is however important to note that business identity is not the same as a business's image. The process of strategic management includes analysis of the internal and external environment, formation of strategy, implementation of strategy, and evaluation of strategy. The theory of strategic management is analyzed within an integrated model of context, content and process. The study established that there are two strategic management approaches to strategic management being employed by businesses in Italy to achieve business identity: The Prescriptive Approach which works best in a stable environment and Emergent Approach which is used in an unpredictable fashion. These approaches are the widely known strategic models and must be examined thoroughly within the context of the fast paced, highly competitive and increasingly dynamic business environment. The prescriptive approach, also known as deliberate strategy is a deterministic and systematic plan of action designed to achieve a specific goal for the long term. It is usually the responsibility of the top management to establish lucid strategic directions through analysis and evaluation and then implement them through the successive layers of the organization. On the other hand, the study established that an emergent strategy approach increases flexibility in times of turbulence and allows the business to respond to opportunities and make the most of the threats. The study recommends that business managers in Italy should strive to adopt the two approaches to strategic management if they were to realize business identity. Keywords: Strategic management, Strategic approaches, Business identity, Brand image.